Vulnerability to Poverty: Tajikistan during and after the Global Financial Crisis - Ira N. Gang; Kseniia Gatskova; John Landon-Lane; Myeong-Su Yun (Global Labor Organization (GLO), 2017)
We examine vulnerability to poverty in Tajikistan during the global financial crisis, focusing on the roles played by international migration and remittances, using a formal, practical, and easily decomposable vulnerability measure. Our strategy is to estimate a Markov transition probability matrix with the aim of identifying the vulnerability of households to poverty. Importantly, by introducing the index of vulnerability as the weighted probability of a household falling into poverty over a given time horizon, we can use the estimated dynamics to assess the short, medium and long-run vulnerability. We find that during the “recession transition” almost all households were vulnerable to poverty while almost none were during the “recovery period”. Overall, urban households, more educated households and households receiving remittances from international labor migrants were less vulnerable to poverty. While households with a current or very recent migrant did not have a significantly lower measured vulnerability to poverty, those households receiving remittances from migrants had a lower vulnerability to poverty. Our findings stress that the international labor migration from Tajikistan may not be considered as a reliable means of welfare security for the households because external economic shocks and internal political decisions may negatively affect Russian economy and lead to a reduction of remittances flow to Tajikistan.
Keywords: J60; D63; I32; 330; mobility measurement; vulnerability; poverty; inequality; measurement; Tajikistan